Evaluation of different chemical preservatives to control Zygosaccharomyces rouxii growth in high sugar culture media - Rojo, María Cecilia; Arroyo Lopez, Francisco Noe; Lerena, María Cecilia; Mercado, Laura Analia; Torres, Adriana Mabel; Combina, Mariana (Elsevier, 2018)
Zygosaccharomyces rouxii is an osmophilic yeast responsible for a large amount of economic loss in high sugar food production. Statistical modelling techniques were used in the present study to assess the individual effects of different chemical preservatives (potassium sorbate, sodium benzoate, dimethyldicarbonate, vanillin, ferulic, p-coumaric and caffeic acids) to control the growth of a cocktail of five yeast strains belonging to this species and isolated from spoilt concentrated grape juices. None of the preservatives assayed were able to completely inhibit the Z. rouxii growth. However, the mathematical models obtained in a high sugar culture media showed that especially four preservatives (potassium sorbate, sodium benzoate, dimethyldicarbonate and vanillin) were the best options to control the growth of this microorganism, obtaining a maximum reduction on yeast growth of approximately 40%. On the contrary, p-coumaric and caffeic acids were the preservatives with the lower effects, which only showed a maximum growth reduction percentage of approximately 15%. Results obtained in this paper could be very useful for industry for a better control of this spoilage yeast in concentrated grape juice.